Solitonic Solutions for Homogeneous KdV Systems by Homotopy Analysis Method - Mohammed Ali; Marwan Alquran; Mahmoud Mohammad (Journal of Applied Mathematics)
We study two-component evolutionary systems of a homogeneous KdV equations of second and third order. The homotopy analysis method (HAM) is used for analytical treatment of these systems. The auxiliary parameter h of HAM is freely chosen from the stability region of the h-curve obtained for each proposed system.